Opioids & organs - O'Neill, Arizona (Drawn & Quarterly, 2026)
"Arizona grieves at the hospital bed of her father, a man she hardly knew, brain dead after a fentanyl overdose. Doctors encourage her to act quickly to recast him as a hero by way of organ donations. Distraught, Arizona makes a decision that will haunt her for the rest of her life. As she struggles to come to terms with her father's death and her role as next of kin in making his life's last decision, she uncovers inconvenient truths about the organ industry's own codependence on the opioid crisis. Her parents were bohemian wild kids of 90s Montreal. He was a talented skateboarder, charming guitarist, and visual artist. She was an aspiring writer and outcast. They lived with other teenagers in the Plateau in a messy apartment filled with drugs, alcohol, and black-market animals. The city's macabre history--McGill Medical School, the Mount Royal Cemetery, ancient cadavers at the Maude Abbott Medical Museum--takes center stage as Arizona sorts out fact from fiction."--Publisher's description.